1968
DOI: 10.1083/jcb.37.3.703
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Metanephric Kidney

Abstract: The metanephric kidney was studied in fetal and older mice beginning at 16 days after mating of the parents. Polyribosomes from fetal kidneys labeled in vitro with 4C-labeled amino acids had 10-20 times more acid-precipitable radioactivity associated with them than polysomes from adult kidneys similarly labeled. Between 3 and 6 days after birth the rate incorporation of labeled amino acids by polyribosomes from neonatal kidneys declined sharply to only twice the value found for adult kidneys. There was no chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
5
9
0
Order By: Relevance
“…Because there is no statistical difference between mean body wt, kidney wt, and renal cortical RNA and DNA content for the twin fetuses, changes in these parameters after removal of one fetus represent a reasonable estimate of the rate of intrauterine growth for the period of observation. Our studies were performed at an earlier gestational age, and in sheep, but are in agreement with the results of Winick and Noble (21) and of Priestly and Malt (18) in demonstrating that, in utero, normal renal growth is mainly by cell division. It should be noted that removal of the first twin in the control studies is a stimulus for noncompetitive enhanced growth, and the observed results are greater than the normal.…”
Section: Discussionsupporting
confidence: 92%
“…Because there is no statistical difference between mean body wt, kidney wt, and renal cortical RNA and DNA content for the twin fetuses, changes in these parameters after removal of one fetus represent a reasonable estimate of the rate of intrauterine growth for the period of observation. Our studies were performed at an earlier gestational age, and in sheep, but are in agreement with the results of Winick and Noble (21) and of Priestly and Malt (18) in demonstrating that, in utero, normal renal growth is mainly by cell division. It should be noted that removal of the first twin in the control studies is a stimulus for noncompetitive enhanced growth, and the observed results are greater than the normal.…”
Section: Discussionsupporting
confidence: 92%
“…(iii) Biochemical methods Techniques used to estimate tissue constituents were essentially those described in Priestley & Malt (1968). Water content was determined when weighed organs were dried to constant weight under vacuum.…”
Section: Materials and Methods (I) Micementioning
confidence: 99%
“…Free amino acid concentrations were measured in postmitochondrial supernatants (20 000 g for 5 min, Sorvall RC 2 centrifuge) by the ninhydrin method of Moore & Stein (1948), as described in Priestley & Malt (1968), using a sample:reagent ratio of 1:10 by volume, and 50 % aqueous ethanol as diluent. The standard curve was prepared with leucine and results were expressed relative to that amino acid.…”
Section: Materials and Methods (I) Micementioning
confidence: 99%
“…It is caused by an increase in protein and RNA levels in the absence of DNA replication [10, 11]. The main support for the role of hypertrophy in the kidney is provided from studies on compensatory renal growth due to a reduction in kidney mass.…”
Section: Hypertrophymentioning
confidence: 99%
“…Hypertrophy has also been suggested to play an instrumental role in the development of glomeruli and the proximal tubules [11, 21, 22]. Yet, an in depth analysis of this process and its underlying mechanism is still lacking.…”
Section: Hypertrophymentioning
confidence: 99%